2006
DOI: 10.1080/14786430600724496
|View full text |Cite
|
Sign up to set email alerts
|

Imperfections in focal conic domains: the role of dislocations

Abstract: It is usual to think of Focal Conic Domains (FCD) as perfect geometric constructions in which the layers are folded into Dupin cyclides, about an ellipse and a hyperbola that are conjugate. This ideal picture is often far from reality. We have investigated in detail the FCDs in several materials which have a transition from a smectic A (SmA) to a nematic phase. The ellipse and the hyperbola are seldom perfect, and the FCD textures also suffer large transformations (in shape or/and in nature) when approaching t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…We will give more details on the mechanisms of the FCD modifications in a forthcoming publication [12]; these mechanisms are also visible in the case of homeotropic samples. Let us conclude by a final remark relating to another type of FCD-dislocations interaction.…”
Section: Conclusion Other Elements Of Discussionmentioning
confidence: 94%
“…We will give more details on the mechanisms of the FCD modifications in a forthcoming publication [12]; these mechanisms are also visible in the case of homeotropic samples. Let us conclude by a final remark relating to another type of FCD-dislocations interaction.…”
Section: Conclusion Other Elements Of Discussionmentioning
confidence: 94%
“…How does an imperfect FCD look? Recently [3,4] we have demonstrated that an imperfect FCD is a Kinked FCD. A kink plays a role of the imperfection on a disclination.…”
Section: Introductionmentioning
confidence: 98%
“…Imperfections in the ideality of FCDs have been recently investigated [9][10][11]; some of these are macroscopic, but most are microscopic, described as ''kinks''.…”
Section: Introductionmentioning
confidence: 99%